Iconography of the Recently Discovered Naga Sculptures from Pamba River Basin, Pathanamthitta District, South Kerala - Ambily C.S; Ajit Kumar and Vinod Pancharath
Recent exploration by the first author brought to light interesting Naga sculptures from the middle ranges of Pamba River basin. All the sculptures are made out of granite and can be classified into Nagarajas and Nagayakshis except one which is a female naga devotee. This paper tries to briefly discuss the iconography, chronology and significance of the sculptures.